Lost in Digital Translations Studies of Digital Resistance and Accommodation to the Welfare State in Practice - Berntsen, Alexander (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Innovations create new possibilities for the welfare state. Digital technologies, however, can create a range of surprising and unintended effects. Lost in Digital Translations: Studies of Digital Resistance and Accommodation to the Welfare State in Practice is an exploration of what happens when digital technologies intersect with welfare state practices. This book seeks to develop a creative critique of digital welfare. Digitalising welfare runs the risk of undermining or suppressing knowledge dimensions that are central in the distribution of welfare - in short, knowledge can be 'lost in digital translation'. The universal welfare state is intended for all citizens. By sensitizing us to what is lost in digital translation, we are made aware of some of the exclusionary mechanisms that impact our digital society. In this anthology a group of researchers investigate how digitalisation influences the most ambitious welfare state in the world: Norway. Given Norway's extensive welfare system, the process of digitalisation has had a profound impact. Digital technologies are used to enhance cooperation and coordination between health trusts and municipalities, standardizing communication between frontline workers and citizens, and even altering the architectural design of public buildings, all of which influences the quality of welfare services. At the same time, patient security is endangered, vulnerable groups experience even more exclusion from society, and for others, the quality of welfare deteriorates.